An unusual presentation of eruptive xanthoma: A case report and literature review. Issue 37 (September 2016) - Kashif, Muhammad; Kumar, Hanesh; Khaja, Misbahuddin
Abstract: Background: Eruptive xanthomas are benign skin lesions caused by localized deposition of lipids in the dermis. The lesions are generally caused by elevated levels of serum triglycerides that leak through the capillaries and are phagocytosed by macrophages in the dermis. Clinical manifestation varies from asymptomatic skin lesions to intense pruritus and tenderness. Methods: We present a case of a middle-aged man admitted with diabetic ketoacidosis secondary to noncompliance with insulin. He was found to have skin lesions as multiple crusted papules on the extremities. Further evaluation revealed elevated serum triglycerides. A diagnosis of eruptive xanthomas was made on skin biopsy, and after starting treatment with lipid lowering agents his cutaneous lesions gradually subsided. Conclusion: Appearance of eruptive xanthomas can signify the onset of serious complications. Prompt recognition of such skin manifestations is warranted to prevent development of fatal medical condition like coronary artery disease and pancreatitis.